2020
DOI: 10.11621/vsp.2020.03.08
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and innovative trends in math education in preschoolers in Russia: Do they fit to educational criteria?

Abstract: Relevance. There is growing interest in the market for educational applications in Russia. A significant number of these are aimed at preschoolers. Although much is known about the key features of preschoolers learning ( due to the cultural-historical approach as well ), there is still little research analyzing whether these features are taken into account in the design and methodology of mobile applications available on the market. Objective. To analyze math apps for preschoolers from the standpoint of cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Why this had to be done was not discussed. Note that analysis of modern Russian programs and mobile apps for preschoolers has shown that the main teaching resource used is the exemplar, a rule taught to the children for performing a task or action by demonstration of the action, while the need to use the mathematical concepts and actions is given as an external condition (Aslanova et al, 2020;Sidneva et al, 2021).…”
Section: Formative Sessionsmentioning
confidence: 99%
“…Why this had to be done was not discussed. Note that analysis of modern Russian programs and mobile apps for preschoolers has shown that the main teaching resource used is the exemplar, a rule taught to the children for performing a task or action by demonstration of the action, while the need to use the mathematical concepts and actions is given as an external condition (Aslanova et al, 2020;Sidneva et al, 2021).…”
Section: Formative Sessionsmentioning
confidence: 99%